Performance Analysis of Data Transmission on a Wireless Sensor Network Using the XBee Pro Series 2B RF Module - I Gusti Made Ngurah Desnanjaya; I Nyoman Buda Hartawan; Wayan Gede Suka Parwita; Ida Bagus Ary Indra Iswara (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
Wireless Sensor Network (WSN) is a wireless network technology that is capable of scanning and can be used to monitor environmental conditions, both indoors and outdoors. One of the devices used in data communication at WSN is XBee. XBee is a device in WSN that uses radio frequency as a data transmission path from one device to another. In sending data, Xbee can be affected by the distance and signal strength between devices. In this research, Xbee communication distance analysis is done outdoors and indoors so as to get data in the form of maximum distance vulnerable from Xbee. The results of this study indicate that the Xbee Pro Series 2B that is measured outside the room is capable of sending data up to a distance of 110 meters, while the Xbee Pro Series 2B device that is measured indoors is capable of sending data up to a distance of 20 meters.